FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN PAJAK DENGAN INDIKATOR TARIF PAJAK EFEKTIF (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2011-2013) (Students' Journal of Accounting and Banking, 2015)
The study examines the effect of firm size, leverage, profitability, fixed asset intensity, inventory intensity, and tax facilities toward tax management using effective tax rate indicator. This research was conducted in Indonesia Stock Exchange by using a go public manufacturing company as the unit of analysis. The research was conducted within purposive sampling method with the sample was taken from the period of 2011 to 2013. The sample collected includes 186 companies which satisfied some criteria. Analysis tool used multiple regression analysis. The result revealed that firm size, profitability, and tax facilities has negative effect and significant to the tax management. Other results revealed that the intensity of fixed assets and inventory intensity has positive effect and significant to the tax management. Whereas the leverage had no significant effect on tax management.Keywords: Tax Management, Effective Tax Rate, Firm Size